Kajian Sketsa Digital dalam Proses Reka-Struktur Bentuk-Bentuk Surface - Riva Tomasowa (Bina Nusantara University, 2013)
Free form surface has a multiple complexity curve intrinsically, so that special approach is needed to form the structure. Geodesic shell is well-known as the shortest path between two points on a curved surface. This method is used to generate the structure of form, which can be easily determined by its basic shape or the complex form. This paper explains how Geodesic theory can assist to generate structures in the early stage of digital sketching. A workshop that has initially started becomes a topic to this discussion. The digital sketching process to apply the theory is the aim of this paper.